THE EFFECT OF DIFFERENT ORGANIC SOLVENTS ON PHYSICOCHEMICALPROPERTIES OF FISH OIL EXTRACT FROM MUDSKIPPER (Periopthalmodon schlosseri) - Edo Pandiangan; Edison Edison; Mirna Ilza (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
ABSTRACTThis study was aimed to determine the physicochemicalproperties of fish oil and to determine the best solvent for dissolving fish oil mudskipper. The method used was an experimental method, with a non-factorial Completely Randomized Design (CRD) consisting of 3 levels of treatment namely, the use of methanol (X1), the use of ethanol (X2), and the use of propanol (X3). The parameters used in the analysis of physicochemical properties were fat content, iodine value, peroxide value, saponification value, color and odor. The results showed that the characteristics of mudskipper fish oil using methanol solvent were fat content of 1.51%, iodine value of 105.79 mgiod/100 g, peroxide value of 3.57 meq/kg, saponification value of 155.79 mgKOH/g, yellow color and fishy odor. Furthermore, the characteristics of mudskipper fish oil using ethanol solvent were fat content of 1.50%, iodine value of 107.59 mgiod/100 g, peroxide value of 3.83 meq/kg, saponification value of 154.95 mgKOH/g, brown color and fishy odor. Moreover, the characteristics of mudskipper fish oil using propanol solvent werefat content of 1.48%, iodine value of 107.98 mgiod/100 g, peroxide value of 3.95 meq/kg, saponification value of 152.21 mgKOH/g, black color and fishy odor.Keywords:Mudskipper fish oil, physicochemical properties, solvent